Political Representation of Disability in Eternals Movie: Between Providing Space or Reinforcing Subjugation - Ikrima, Nabila (State Islamic Institute of Bone, Indonesia, 2023)
This research aims to reveal the meaning behind the representation of disability in the film Eternals using Stuart Hall's representation theory approach and Roland Barthes' semiotic method. Eternals first presented the figure of Makkari who is also a nuisance in the real world. The research results show that the representation of Makkari as a person with a disability is still shown as a marginal, incompetent figure, and only a supporting character in the film.